2021
DOI: 10.3390/su131910589
|View full text |Cite
|
Sign up to set email alerts
|

PLM Solutions in the Process of Supporting the Implementation and Maintenance of the Circular Economy Concept in Manufacturing Companies

Abstract: The Circular Economy (CE) is a priority topic for various stakeholders such as politicians, scientists, and industry. However, despite the significant interest in CE, there is still a lack of a framework explaining how manufacturing companies willing to become circular adapt their existing business model. The concept of this work is based on the use of Information Technologies such as the well-known and long-proven Product Lifecycle Management (PLM) solutions in the implementation and maintenance of the CE con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This integration enhances the accuracy of material data, improves supply chain transparency, and streamlines decision-making [22,23]. Lastly, a PLM ensures a holistic approach to sustainable construction, enabling better-informed choices throughout the entire project life cycle [24].…”
Section: Product Lifecycle Management Softwarementioning
confidence: 95%
“…This integration enhances the accuracy of material data, improves supply chain transparency, and streamlines decision-making [22,23]. Lastly, a PLM ensures a holistic approach to sustainable construction, enabling better-informed choices throughout the entire project life cycle [24].…”
Section: Product Lifecycle Management Softwarementioning
confidence: 95%
“…Siguenza et al [178] studied the washing machine market and recommended implementing a pay-per-wash model and product leasing to improve material usage efficiency. Cholewa & Minh [179] discovered that PLM systems help enhance CE concepts in manufacturing by aiding product creation, promoting transparency, and maximizing value.…”
Section: Product Lifecycle Management (Plm)mentioning
confidence: 99%
“…The ECO-Service Design (ECO-SD) method, which integrates ecologic design and service design to create new ecologically sustainable services [14], can correlate the environmental criteria from the ecological design with a human-centered approach. Other studies illustrated how the use of information technologies-such as product lifecycle management (PLM) in the implementation and maintenance of the CE idea-may help to support and assure a successful process for the circular economy principles [16].…”
Section: Management-mmentioning
confidence: 99%
“…Studies have shown that the use of information technologies-such as product lifecycle management (PLM) in the implementation and maintenance of the CE concept-may support and ensure an effective process for the circular economy concepts [16], given that the impact of the Industry 4.0 concept has grown in multiple directions.…”
Section: Management-mmentioning
confidence: 99%